Language and Content in Graffiti: A Case of Chittagong - Hossain, Ghazi Shahadat (Nepalese Linguistics, 2022)
This study analyzed the content and language in graffiti prevailing in Chittagong. The aim of the research was to examine how and why graffitists utilized graffiti. The data were collected from various places of Chittagong. Two frameworks i.e., Fairclough’s critical discourse analysis and Brown and Clarke’s thematic content analysis, were used to analyze data and the research method used in this study was qualitative. The findings reveal that graffitists used this form of art for a variety of purposes (such as political ideologies, social concerns) and they used diverse codes to express their meanings.